Diet versatility in cowpea ( Vigna unguiculata) genotypes - DE, NIRMAL; KUMAR, RAJ; KALLOO, G (The Indian Journal of Agricultural Sciences, 2014)
A tield experiment was conducted during the rainy (kharif) season of 1998-99 on 20 genotypes of cowpea [Vigna unguiculata (L.) Walp.] in field under in-situ condition on a well-drained. sandy-loam soil of Inceptisol origin, to study the protein content and Ca : P ratio of the edible plant parts. The mean prptein content of cowpea foliage was 20.3% with ca: P ratio of 2. 7 when harvested belbre flowering stage (25 days after sowing). At 45 days after sowing, the mean leaf protein content of 20 genotypes was 18.2% with Ca: P ratio of2.6 and the pod protein content was 20.6 %. In traditional seed harvest treatment (75 days after sowing). the protein content of cowpea foliage dropped to 10.9%, the Ca : P ratio was 6.5 and the pod plus seed protein content was 21.2 %. Sufficient level of available Ca (0.98 to 1.8%) was present in edible portion of cowpea foil age throughout the crop-growth stage. An increase of Ca content and decrease of P content were observed with crop maturity from pre-flowering to harvesting stage for all the varieties. The yield potentiality of (HR Sel II’ and ’Se1 2-1’ genotypes was higher among 20 tested varieties. High protein content in both foliage and pod or seed, throughout the growth stage was recorded in ’Pusa Komal’. The protein content of ’IHR Sel II’ and ’Sel 2-1’ was also statistically at par with ’Pusa Komal. In general higher protein content was recorded in local genotypes like ’Red Seeded Climbing’. ’Cowpea Local 1’ and ’Kalajhambla’ (bush) compared with the other tested genotypes.